Patients' experiences and satisfaction with health care in the Salah Azaiez Institute of Cancer in Tunisia in 2020 - Hyem Khiari; Marwa Chraiet; Rym Mallekh; Ines Cherif; Mohamed Hsairi (The Beryl Institute, 2021)
Measurement of patient-centered care is a key step to ensure quality of care improvement. The aims of this study were to evaluate the experience of hospitalized patients of Salah Azaiez Institute (SAI) of Cancer of Tunisia in 2020 and to analyze factors associated to the global satisfaction. It was a cross-sectional study. The used questionnaire was derived from the Picker patient questionnaire. Factors associated to the global satisfaction were assessed using Chi-squared and Fisher's exact tests. The present study concerned 200 inpatients of the SAI. The Cronbach's α of the patient experience test (PPE-15) was of 0.82 indicating a good internal consistency. According to results of this study, only 38.5% of the patients were satisfied with their hospitalization. Perception of the quality of the received treatment was good to excellent for 57.0%. Regarding the global organization, 56.5% of the patients found it intermediate and 21.5% perceived it as bad. The highest scores among patient experience dimensions concerned the coordination of healthcare, the respect for patient preference and the physical comfort. However, lowest scores were attributed to the involvement of family and friends, the information and patient education and the emotional support. Unlike socio-demographic factors, patient experience and its dimensions was strongly associated to the global satisfaction. Further studies are recommended to explore patient experience dimensions and other determinants of patient satisfaction in Tunisia. Experience Framework This article is associated with the Policy & Measurement lens of The Beryl Institute Experience Framework. (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Policy%20%26%20Measurement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.